Transformasi UMKM Kuliner: Strategi Pengembangan Ekonomi Kreatif di Era Digital Untuk Meningkatkan Kesejahteraan Keluarga - Irawati, S. Anugrahini; Wantara, Pribanus; Arfy, Widya Rizka (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
This study aims to explain how the transformation of culinary MSMEs in the digital era is a strategic step in developing the creative economy, which plays an important role in improving the welfare of culinary MSME family actors in Sampang Regency. This study was conducted using an interactive qualitative approach. While the selection of informants was carried out using the purpose sampling technique. Based on the results of the study, it shows that the development strategies that can be applied by culinary MSMEs; I Application of Digital Technology in Culinary MSMEs through e-commerce platforms, delivery service applications, social media and digital marketing. 2. Creative Economy Development Strategy through product innovation, collaboration and partnerships and customer experience 3. Improving Family Welfare seen from increasing income, improving quality of life, sending children to higher education, economic stability, self-development. This strategy is important so that culinary MSME actors can survive and develop in the long term. Based on the research results, it is known that this strategy can really be implemented and improve family welfare.